Mycotoxicity of leaf extract of Tabernaemontana pachysiphon Stapf against Fusarium oxysporum Schlecht, a postharvest fungal rot pathogen of taro - Enyiukwu, David Nwazuo; Amadioha, Anderson Chidi; Bassey, Inemesit Ndareke (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2024)
Taro, otherwise known as cocoyam, is one of the major sources of calories in the tropics. However, losses of its corm during storage are high, partly due to pathogenic diseases. Fusarium oxysporum is one of the principal fungal pathogens causing about 50% of postharvest losses of taro corms in the tropics. The rise in pesticide-resistant fungal pathogens, amongst other factors, has necessitated the recent search for alternatives to synthetic pesticides. This work aimed to evaluate the effects of six concentrations (0%, 10%, 20%, 30%, 40%, and 50%) of aqueous leaf extract of T. pachysiphon on spore germination, mycelial growth and reproduction of F. oxysporum both in vitro and in vivo. The in vitro experiment was conducted using the poison bait technique, while the in vivo experiment involved 21 corms (200 g) artificially infected with F. oxysporum and treated with the respective concentrations of the test extracts or griseofulvin. The control consisted of fungus-infected corms only. Generally, the experiments consisted of 7 treatments replicated 3 times and were laid out in a completely randomized design. Results of the cultures studies showed that all aqueous extract of T. pachysiphon significantly (P< 0.05) and to varying degrees impeded spore germination (56.38–70.24%) and retarded radial growth of the pathogen (68.27–82.01%). The percentage rot expression in the living tissues treated with the extracts ranged between 19.4% and 40.4%. All results were statistically (P< 0.05) superior to the control but comparable to the results (75.06%, 86.41%, and 17.2%) obtained with griseofulvin for these features, respectively. The inhibitions were linearly correlated with the dose of application of the biotoxicant both in vitro and in vivo.